El paseo de Rosie - Hutchins, Pat, 1942-; Ada, Alma Flor. (New York : Aladdin Paperback/Libros Colibri, 1997)
Although unaware that a fox is after her as she takes a walk around the farmyard, Rosie the hen still manages to lead him into one accident after another.
Keywords: Chickens -- Fiction; Foxes -- Fiction; Spanish language materials